Pedagogical technologies in the formation of creative competence in the educational process - Ulukhanov Ibrokhim Tokhtakhojaevich; Khusainova Gozal Abdurasulovna; Ubaydullaev Solijon Kadyrovich (Zien Journals, 2022)
The article describes the ways and stages of developing students' creative abilities in the educational process.
Keywords: Problem situation; professionalism; special ability; creativity; thinking